Microbial biofilms: molecular mechanisms of antibiotic resistance and methods for their investigation - O. Yu. Koshova; O. V. Shapovalova; N. I. Filimonova (One Health Journal, 2026)
By performing a literature review, to summarize current evidence on the molecular mechanisms underlying biofilm-associated resistance to antibacterial agents and to analyze laboratory approaches used for biofilm cultivation, visualization, and antimicrobial susceptibility assessment. An analytical review of Ukrainian and international publications on biofilms, antimicrobial resistance, and biofilm research methods was performed. Sources were identified through open scientific databases and library resources, including PubMed, Google Scholar, ScienceDirect, SpringerLink, Scopus, and domestic library collections. The search strategy included terms related to biofilms, bacterial biofilms, antimicrobial resistance, antibiotic tolerance, molecular resistance mechanisms, biofilm research methods, and biofilm-associated infections. The review demonstrates that biofilm resistance is a multifactorial phenomenon generated by the combined action of several protective layers. A central role belongs to the extracellular matrix, which contains exopolysaccharides, proteins, lipids, and extracellular DNA and acts as both a structural scaffold and a diffusion barrier. Biofilm tolerance is further reinforced by marked spatial and metabolic heterogeneity, limited antibiotic penetration into deeper layers, the emergence of dormant persister cells, reduced growth activity, efflux-mediated drug removal, enzymatic antibiotic inactivation, target modification, and dissemination of antibiotic resistance genes. Together, these factors markedly decrease the susceptibility of biofilm-embedded microorganisms compared with planktonic cells. The paper also systematizes the main laboratory models used to study biofilms. Static systems, including tube assays, Congo Red Agar, and microtiter plate methods, are suitable for primary screening and quantitative biomass assessment, but only partially reproduce the gradients and hydrodynamic conditions typical of natural and clinical environments. Dynamic models, such as flow-cell systems, drip-flow reactors, rotating disk reactors, and CDC biofilm reactors, allow mature biofilms to be formed under controlled flow and shear conditions, although they require more complex instrumentation. Special attention is given to methods for testing biofilm susceptibility, including CFU counting, MBEC-based approaches, MBC-B determination, and metabolic viability assays, which provide a more informative comparison of antibiotic activity against planktonic and biofilm populations. Biofilm-associated resistance cannot be attributed to a single determinant, since it arises from the interaction between matrix-mediated protection, physiological heterogeneity, adaptive phenotypic states, and genetic resistance mechanisms. Existing in vitro models have significantly improved the study of biofilm biology and antimicrobial susceptibility, yet none is universally applicable to all research and clinical tasks. Further development of standardized and reproducible methods that retain ecological and clinical relevance is essential for better diagnostics and for designing more effective strategies against biofilm-associated infections.